CHARGER BACKUP : uma solução para salvaguarda de dados - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The rapid growth in the use of mobile devices in recent years has made available a number of features. Which attract users to store their data on these devices, thus intensifying concern about the security of this information. The proposal of this research is the creation of a model for the safeguarding of data, in devices that use the Android platform, aiming for simplicity, transparency and efficiency. Define techniques for performing backup and restoration of data, compaction procedures, and storage media. The methodology employed in this project makes use of the scientific method. Applying the techniques of systematic observation, description of the techniques observed and comparison of the various methods of safeguard currently used. In possession of this information, a model for data backup is created. To carry out the implementation a survey of the necessary requirements was made. After the implementation was completed, the validation of the model was performed, where the tests were performed and the results analyzed. Through this, it can be concluded that the objective of this work has been reached.
Keywords: Android; Backup; Dispositivos Móveis; Android; backup; mobile devices; CNPQ::ENGENHARIAS